The Effects of Overall Service Quality, Customer Value, Customer Trust, and Customer Satisfaction on Customer Loyalty in the Hotel Industry - Joshua Joviando; Kurniawati Kurniawati (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2022)
This study examines the relationship between hotel customer loyalty and service quality, customer value, customer trust, and customer satisfaction. It aims to validate a previously unidentified theoretical model in the Indonesian hospitality industry. This study employs a quantitative approach. First, a survey was distributed to 181 guests of four-star hotels in Jakarta. Information regarding service quality, customer value, customer trust, and customer satisfaction was gathered through surveys. Then, PLS-SEM was utilized to analyze the collected data and establish the proposed Structural Equation Model (SEM). The findings indicate that service quality positively influences customer value, trust, and satisfaction. This study found no correlation between customer trust and customer loyalty. However, there is a positive correlation between customer satisfaction and customer loyalty, as demonstrated by the test. Additionally, customer value was found to influence customer loyalty positively. As a result, the suggested model helps hotel owners create a program to improve their customer service in order to increase customer trust, satisfaction, value, and loyalty and so raise the profitability of the sector. By validating the suggested structural model and offering insight into consumer perceptions, this research benefits the hotel services industry. Hotel operators will be better able to incorporate service quality to increase customer trust, satisfaction, value, and loyalty.